ANALYSIS OF PUBLIC RELATIONS STRATEGY OF ELIM RANTEPAO HOSPITAL IN MAINTAINING HOSPITAL IMAGE IN THE PANDEMI ERA - Musyawir, Andi Khaerul; Allolayuk, Austin Icha Restha (Homes Journal: Hospital Management Studies Journal, 2023)
In minimizing anxiety and worries as well as rebuilding consumer confidence so that they are willing to use health services in the midst of the covid-19 pandemic, there is an appropriate communication strategy from management of health services. One of the communication that is considered appropriate in overcoming this unfavorable event is to perform the roles and functions of public relations properly. This study aimed to explain the Strategic Public Relations of Elim Rantepao Hospital in Maintaining the image of the Hospital in the Era of the COVID-19 Pandemic. This type of research used qualitative research methods. Methods collected documentation data and in-depth interviews to obtain information. From the aspec of public relation communicator in providing information to the public through social media such as Facebook, Instagram, and Youtube. Aspects of relationship Public Relations Elim Rantepao Hospital seeks to establish good relationships with the community, for example providing education to the community through social media on how to deal with the Covid situation. And support activities carried out by public relations. Aspects of Good Image Maker Public Relations of Elim Rantepao Hospital as a buider and creator of a positive image of the organization by providing open services to the public where open aservices can be accessed by the public with communication media used by public relations, namely Facebook, Instagram, WhatsApp, and YouTube. The public relations strategy of Elim Rantepao Hospital in maintaining the image of the hospital during the pandemic is the educate the public about COVID-19, promote health promotion and hospital marketing, public relations as a mediator also connects the hospital and the community. Public relations needs to hold a family gathering in order to further strengthen the relationship between fellow employees.